Venture Capital Industry in China - Yang, Yiqing (2007)
This study utilizes the venture capital industry in the West as a base to examine the characteristics of China's venture capital industry. Based on questionnaire and interview survey, I find reasonably consistent views around the world on the relative importance of various venture capitalist roles. However, the findings present that how those roles are implemented, how investor/investee relationship is developed, and how VCs is managing their firms, largely vary in different regions, and shaped by many influences, such as historical reasons, culture and cognitive differences, government systems, and institutional environment. It seems that a model stated in western literatures is not valid in China. Further, the study suggests that venture capital industry is vital for the innovation and industrialization of Chinese economy, and several recommendations for both government on macro intervention and VC firms on upgrading of professional are presented.